Instagram Use and First-Year College Students' Social Adjustment - Elok D. Malay (Fakultas Psikologi Universitas Pancasila, 2019)
Despite many research on the relation between social media and college students, the results are still varied. Moreover, a study that focuses on patterns of social media use is still limited, especially in Indonesia. Therefore, this study tested the relationship between patterns of Instagram (IG)-a popular social media in Indonesia-use and social adjustment of the first-year college students. This correlational study involved 137 college students in Jakarta Greater Area. Data were gathered using The Instagram Perceived Use Scale and The Social Adjustment subscale of The Student Adaptation to College Questionnaire (SACQ). The multiple regression statistical analysis showed that among four patterns of IG use, only three patterns related to the freshmen' social adjustment. They were the pattern of maintaining a social connection (MSC), sharing and seeking personal information (SSPI), and gaming (GAME). Furthermore, MSC was the only significant predictor to college freshmen's social adjustment. Meanwhile, there was no correlation between social adjustment and using IG for pursuing social romantic or sexual relationships (PRSR). In conclusion, IG use could significantly predict first-year college students' social adjustment as long as the usage is intended to maintain their social connections.